Peran Penyuluh Bidang Keluarga Sakinah dalam Menganlisis Kesiapan Psikologis Calon Pengantin Melalui Pembekalan Catin di KUA Kecamatan Kanigaran Kota Probolinggo - Nasirudin Al Ahsani; Rif'atul Khasanah (Jurnal Al-Hikmah, 2022)
The divorce rate in Indonesia is still high, so the impact is not only between husband and wife, but also has an impact on the children and families of both parties. Divorce usually begins with an ongoing conflict in the household. Lack of psychological readiness by each partner that can trigger the conflict. The purpose of this study is to see if there is a role for the sakinah family extension worker in analyzing the psychological readiness of the prospective bride and groom through catin debriefing at the KUA, Kanigaran District, Probolinggo City. The research method uses a qualitative method with data collection techniques in the form of observation and interviews. The results of the research obtained were that the KUA extensionist in Kanigaran Subdistrict had a very important role in analyzing the psychological readiness of the prospective substitute. The supply of catin done by KUA Kanigaran sub-district is a form of effort to provide assistance to the bride and groom in order to achieve stability to understand each other and accept each other.